Successful Management of Macerated Fetus in A Marathwadi Buffalo - Waykule, Shraddha; Patil, Anil; Ramteke, Snehal; Bhosale , Yogesh (The Indian Journal of Animal Reproduction, 2025)
A ten-month pregnant, six year old Marathwadi buffalo in her third party was presented with the history of anorexia, straining and foul smelling reddish discharge from vulva for 2 days. Per-rectal exam revealed a contracted uterus posi tioned at the pelvic brim, with a thickened uterine wall and bony prominences of a hard fetal mass felt. The placentomes were not palpable, and fremitus was absent. Per-vaginal examination revealed a completely dilated cervix. Therapeutically Managemental strategies for the treatment of macerated fetus typically includes manual removal of the macerated bony fetal parts along with uterine flushing/douching and prompt treatment with fourth generation antibiotics, uterine oral ecbolics and gluconeogenic precursors helps in achieving uneventful recovery within three days in Marathwadi Buffalo.
Keywords: Autolysis; Fetal maceration; Marathwadi buffalo; Uterine lavage